LOCATING WOMEN IN JIHAD: THE CASE OF WOMEN IN THE ISLAMIC STATE OF IRAQ AND SYRIA (ISIS) - Khelghat-Doost, Hamoon (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The increase in women’s engagement with jihadi groups around the globe fueled debates regarding women’s incorporation into jihadi organizations. The current trend in the global labor force clearly demonstrates a discriminatory pattern in favor of men. Surprisingly, despite this traditional restrictive view of Islamic jurisprudence on women’s social activities, the level of women’s incorporation into jihadi organizations has grown rapidly both in numbers and roles. Before the defeat of the organization in late 2018, nearly 20 percent of all members of the Islamic State in Iraq and Syria (ISIS) were women. As ISIS morphed beyond a mere militant organization and into a state builder, its utilization of women also transformed accordingly to address the challenges that a functioning state faces. By using primary data collected from several field trips in the Middle East, this article argues the position of women in ISIS and the mechanisms by which they were incorporated.